On the Laplacian spread of graphs - You, Zhifu,; Liu, Bolian, (Utilitas Mathematica, 2013)
Let μ1 < μ2 <⋯ < μn be the Laplacian eigenvalues of a graph. The Laplacian spread is defined as LS(G) = μ1 - μn-1. In this paper, the integral and equi-Laplacian spread of graphs are obtained. Moreover, the Laplacian spread of regular graphs are considered. Finally, we discuss the maximum Laplacian spread of graphs with given order.